2017
DOI: 10.1080/14616734.2017.1293703
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and attachment in early childhood: a series of meta-analyses

Abstract: Empirical findings regarding the association between child attachment and sleep have been inconsistent. The objectives of this series of meta-analyses were to assess the size of the association between child sleep and attachment and to examine whether study methodology (attachment measure, sleep measure) and age moderate this association. Sixteen studies (2783 children aged from 6 to 38 months) were included. Significant associations were found between attachment security and sleep efficiency (r = .18) and att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…There were no significant direct associations between crying and sleeping problems and formation of insecure attachment, but there was a small indirect association between crying and sleeping problems and insecure attachment via higher levels of maternal depressive symptoms at 6 months. Our finding is in accordance with Simard et al (2017) who found no association between sleep and secure attachment when sleep was assessed before 15 months of age. Further, our finding is consistent with attachment theory, which postulates that the development of insecure attachment patterns is predominantly explained by mothers' ability to be sensitive to their infants' cues rather than infant-related characteristics (Ainsworth et al, 1978;Bowlby, 1969).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…There were no significant direct associations between crying and sleeping problems and formation of insecure attachment, but there was a small indirect association between crying and sleeping problems and insecure attachment via higher levels of maternal depressive symptoms at 6 months. Our finding is in accordance with Simard et al (2017) who found no association between sleep and secure attachment when sleep was assessed before 15 months of age. Further, our finding is consistent with attachment theory, which postulates that the development of insecure attachment patterns is predominantly explained by mothers' ability to be sensitive to their infants' cues rather than infant-related characteristics (Ainsworth et al, 1978;Bowlby, 1969).…”
Section: Discussionsupporting
confidence: 93%
“…Even if they do wake, they may be less anxious and so easily fall back to sleep, whereas infants who have problems settling to sleep and wake up frequently during the night are likely to be more anxious about night-time separation. Indeed, a recent meta-analysis of 16 studies found that sleep problems were significantly associated with both secure and in particular, insecure-resistant attachment (Simard et al, 2017). However, this meta-analysis study did not evaluate disorganized attachment and the majority of included studies assessed sleep on 12-month old infants or older.…”
Section: Infant Regulatory Problems and Attachmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Ventilation systems may be far from ideal, as high levels of allergens can affect the children's sleep quantity and quality. 18 Maternal education level may affect the way mothers take care of their children. As parenting patterns are closely related to child development, higher parental education may lead to more informed and better care of children, thus positively affecting child development.…”
Section: Discussionmentioning
confidence: 99%
“…The link between sleep problems in very early life and behavioral and sleep problems in later childhood may be, paradoxically, mediated by the widespread sociocultural and clinical application of sleep training or FWB strategies, resulting in cascades of both parent and infant chronic SNS-HPA hyperarousal (Simard et al, 2017; Williams et al, 2017; Ball et al, 2018). FWB approaches also disrupt the dyadic synchrony of the circadian clock, by promoting long blocks of sleep during the day (Thomas et al, 2014).…”
Section: Biology-culture Mismatch In Very Early Life Generates Enviromentioning
confidence: 99%